Different Extracellular β-Amyloid (1-42) Aggregates Differentially Impair Neural Cell Adhesion and Neurite Outgrowth through Differential Induction of Scaffold Palladin - Tianyu Zhang; Chuli Song; He Li; Yanru Zheng; Yingjiu Zhang (Biomolecules, 2022)
Extracellular amyloid β-protein (1-42) (Aβ42) aggregates have been recognized as toxic agents for neural cells in vivo and in vitro. The aim of this study was to investigate the cytotoxic effects of extracellular Aβ42 aggregates in soluble (or suspended, SAβ42) and deposited (or attached, DAβ42) forms on cell adhesion/re-adhesion, neurite outgrowth, and intracellular scaffold palladin using the neural cell lines SH-SY5Y and HT22, and to elucidate the potential relevance of these effects. The effect of extracellular Aβ42 on neural cell adhesion was directly associated with their neurotrophic or neurotoxic activity, with SAβ42 aggregates reducing cell adhesion and associated live cell de-adherence more than DAβ42 aggregates, while causing higher mortality. The reduction in cell adhesion due to extracellular Aβ42 aggregates was accompanied by the impairment of neurite outgrowth, both in length and number, and similarly, SAβ42 aggregates impaired the extension of neurites more severely than DAβ42 aggregates. Further, the disparate changes of intracellular palladin induced by SAβ42 and DAβ42 aggregates, respectively, might underlie their aforementioned effects on target cells. Further, the use of anti-oligomeric Aβ42 scFv antibodies revealed that extracellular Aβ42 aggregates, especially large DAβ42 aggregates, had some independent detrimental effects, including physical barrier effects on neural cell adhesion and neuritogenesis in addition to their neurotoxicity, which might be caused by the rigid C-terminal clusters formed between adjacent Aβ42 chains in Aβ42 aggregates. Our findings, concerning how scaffold palladin responds to extracellular Aβ42 aggregates, and is closely connected with declines in cell adhesion and neurite outgrowth, provide new insights into the cytotoxicity of extracellular Aβ42 aggregates in Alzheimer disease.